Correlation of Hysterosalpingography Findings with Laparoscopic Evaluation in Women with Primary Infertility - Abeera Sajid, Sohaila Ameen, Rabia Razaq, Zareena Begum, Zahra Ali, Sanjay Kumar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hysterosalpingography (HSG) is a commonly used first-line investigation for evaluating tubal patency in women with infertility. Objective: To assess the correlation between HSG findings and laparoscopic evaluation in women with primary infertility and to determine the diagnostic accuracy of HSG in identifying tubal and pelvic abnormalities. Methodology: This was a cross-sectional analytical study conducted at Lahore General Hospital from August 2021 to January 2022. A total of 110 women with primary infertility were enrolled in the study. A pre-designed proforma was used to record demographic details, HSG results, laparoscopic findings, and relevant clinical history. Eligible participants underwent a structured evaluation comprising HSG followed by diagnostic laparoscopy. HSG was performed in the follicular phase (day 7–10) using a standard technique with contrast dye. Results: HSG revealed normal findings in 40.9% of participants, while 24.5% had unilateral block, 16.4% bilateral block, and 9.1% showed hydrosalpinx. Laparoscopy confirmed tubal patency in 36.4%, unilateral block in 22.7%, bilateral block in 18.2%, with additional findings including peritubal adhesions (11.8%) and endometriosis (7.3%). HSG demonstrated a sensitivity of 88.2%, specificity of 91.1%, and overall diagnostic accuracy of 89.4%, with a kappa agreement value of 0.77 indicating substantial agreement with laparoscopy. However, concordance for hydrosalpinx detection was low (40%). Conclusion: HSG demonstrates good correlation with laparoscopic findings in evaluating tubal pathology among women with primary infertility. It is an effective initial screening tool due to its high sensitivity and non-invasive nature. Keywords: Primary infertility, hysterosalpingography, laparoscopy, tubal block, pelvic adhesions.